Informaciones ecológicas sobre Coprophaneus (Coprophanaeus) Telamon nevinsoni Arnaud & Gamez (Coleoptera: Scarabaeinae: Phanaeini) en un sector de Selva Húmeda Submontana en Mérida, Venezuela - Gámez, Jorge; Mora, Enrique; Acconcia, Raffaele (Instituto de Ecología, A.C., 2006)
The subspecies Coprophanaeus (Coprophanaeus) telamon nevinsoni Arnaud & Gámez was analyzed in forest and in a mixed plantation using necrotraps in order to study the daily and annual activity, and the using of the space and the bait that was placed artificially in order to observe how it uses carrion resource. It was collected during the year. Its biggest abundance was registered in the two of maximum precipitation (83, 63%). It uses either the forest or agriculture environment, it doesn’t matter which takes advantage of the vegetation corridors, mostly those which have arboreal and shrub elements. It shows bimodal daily activity exclusively circumscribed at the twilight in the contrasting environments evaluated. This happens with more temporal amplitude in the forest environment. It may use different sizes carrion resource, because they are capable to transfer it from the aggregation point to the supplying galleries where they bury the carrion. It big pieces, the beetles take the carrion from the parcial burial and take them to storage cavities and galleries. These subspecies represent the most influent beetle in terms of carrion disposition in the studied environments. Its extinction is feasible due to the antropic action, fundamentally for elimination of the relicts existent forest.